2020
DOI: 10.3390/pathogens9100778
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Risk Reduction of E. coli Transmission after Using Antimicrobial Hand Soap

Abstract: Handwashing with soap is an effective and economical means to reduce the likelihood of Escherichia coli infection from indirect contact with contaminated surfaces during food preparation. The purpose of this study was to conduct a quantitative microbial risk assessment (QMRA) to evaluate the risk of infection from indirect contact with fomites contaminated with E. coli after hand washing with antimicrobial hand soaps. A Monte Carlo simulation was done with a total of 10,000 simulations to compare the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our data also revealed that Canteens and Retirement Homes/Day Care Centers had a high proportion of samples taken from hands of food handlers classified as "unsatisfactory", denoting less adherence to handwashing practices. Indeed, it has been reported that a reduction occurs in counts of Enterobacteriaceae, including E. coli after hand washing, particularly when food handlers use antimicrobial hand soap [11,20]. Additionally, the evaluation of hygienic patterns of the hands of manipulators in different food units also showed that more than 10% of positive samples for S. aureus were found in Fishmongers (14.3%), Schools/Kindergartens (12.1%) and Pastry/Bakery establishments (11.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also revealed that Canteens and Retirement Homes/Day Care Centers had a high proportion of samples taken from hands of food handlers classified as "unsatisfactory", denoting less adherence to handwashing practices. Indeed, it has been reported that a reduction occurs in counts of Enterobacteriaceae, including E. coli after hand washing, particularly when food handlers use antimicrobial hand soap [11,20]. Additionally, the evaluation of hygienic patterns of the hands of manipulators in different food units also showed that more than 10% of positive samples for S. aureus were found in Fishmongers (14.3%), Schools/Kindergartens (12.1%) and Pastry/Bakery establishments (11.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a pathogenic microorganism can remain viable in cutting boards and food contact surfaces [6][7][8] demanding the rigorous cleaning and disinfection of kitchen utensils, equipment and surfaces [9,10]. Hands of food handlers have also been considered an important determinant of microbiological contamination of food and washing hands plays a valuable role in preventing the transmission of foodborne illnesses [4,11,12]. Staphylococcus aureus colonizes the nasopharynx of asymptomatic carriers leading to the contamination of the hands of food handlers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Washing hands with water and soap reduced the risk of foodborne illnesses during multiple contamination scenarios (i.e., transfer of E. coli from cutting board surface to hands, kitchen sponge to hands, etc.) by approximately 5 times compared to no handwashing [3] and reduced Enterococcus concentrations from farmworkers' hands (1.6 log 10 reduction) [22].…”
Section: Introductionmentioning
confidence: 98%
“…In 2019, The European Food Safety Authority (EFSA) reported 5175 foodborne outbreaks that affected 53,383 people; inadequate consumer hygiene practices in the household being the most commonly reported source (41.3%) [2]. Foodborne diseases are preventable, and proper hand hygiene has been acknowledged as one of the most simple and adequate measures to prevent or reduce the infection rate with foodborne pathogens and the number of cases of foodborne illnesses, which usually occur through inefficient hand hygiene, cross-contamination, and transmission of certain bacteria and viruses [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…c. Position The product "Scalila Surprise Hand Soap" is positioned as a practical hand soap containing antibacterial which attracts children's attention to wash their hands regularly with soap because of its unique and cute shape [8].…”
Section: Introduction 11 Market Surveymentioning
confidence: 99%